Drilled Shaft Socket Connections for Precast Columns in Seismic Regions - Tran, Hung Viet (My University, 2015)
A new type of connection between a precast concrete column and a drilled shaft has been developed for Accelerated Bridge Construction (ABC) in regions of moderate or high seismicity. This connection can be built quickly and allows generous placement tolerances. Three quasi-static tests of connections between a precast bridge column and a drilled shaft were performed (1) to investigate the seismic performance of this connection, and (2) to calibrate a new design methodology. The test specimens represented the most critical geometry in which the difference between the diameters of the shaft and column was minimized. Large-scale, lateral-load tests to a drift ratio of 10% showed that, if adequate confining steel is included in the splice zone, the plastic hinging mechanism forms in the column, without inducing damage in the splice or shaft. If the confinement is insufficient, the strength of the splice zone deteriorates rapidly with cyclic loading. A new design methodology, based on a strut-and-tie model of the transition region, allows the designer to proportion the connection to limit the strains in the connection transverse reinforcement.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: accelerated bridge construction; drilled shaft; precast concrete; Rapid construction; seismic region; socket connection; Civil engineering; civil engineering